Peningkatan Aktivitas dan Hasil Belajar Fisika melalui Pembelajaran Kooperatif Jigsaw di SMP - Alamsah, Abdul Haris (Muhammadiyah University Press, 2016)
The learning process is still dominated by the activities of the lecture so that less active learners. This will have an effect on activity and learning outcomes obtained learners in physics. To overcome the need for a suitable learning model so that students are more active and kretif in solving a problem that is by learning model Jigsaw. The purpose of research, the implementation of cooperative learning model Jigsaw can improve Physical activity and learning outcomes for students of class IX B SMP Negeri 16Surakarta, the first half of the year 20014/2015. This research is a classroom action research conducted in two cycles, each cycle consisting of planning, action, observation and reflection. Data obtained in this research include the study of students, learners and the level of activity observed in response to the results of the process pebelajaran. Indikator success when the average daily test results have been achieved> KKM. The results of the study, by using model Jigsaw can increase the activity and learning outcomes of students of class IX B SMP N 16 Surakarta academic year 20014/2015.